Frasa Adjektiva dalam Bahasa Bolakme: Kajian Semantik - Yohanes Lose Dasilva; Febronius Densius Naja; Amelia Kaisiepo; Sutarman Borean (DEIKTIS: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This research aims to analyze adjectival phrases in the Bolakme language from a semantic perspective. The main focus of this research is on the form, structure, and meaning of adjectival phrases, as well as their comparison with equivalents in Indonesian to reveal the distinctive nuances of meaning in the Bolakme language. This research uses a descriptive qualitative approach, with data sources consisting of 30 adjectival phrases obtained through interviews, direct observation, and documentation. The sample was taken using purposive sampling with a total of 10 native Bolakme speakers as informants. The analysis technique uses meaning and context analysis methods. The research results show that adjectival phrases in the Bolakme language have a wealth of forms and meanings. Some phrases are formed by the repetition of morphemes to emphasize meaning, such as arek-arek which means "suddenly”. Phrases like maluk ekerak (failed) depict a combination of the meanings "dishonorable" and "fall," indicating a total failure. The phrase in egen amberi, which means "original," reflects a strong cultural identity. The phrases porok jegerak (absorbed) and wagangge (accepted) have deep semantic meanings related to the processes of social and psychological acceptance. In some cases, a word like maluk has a dual meaning, namely "despicable," "ugly," or "damaged," depending on the context. Thus, it can be concluded that adjectival phrases in the Bolakme language not only contain descriptive information but also reflect the worldview, cultural values, and collective experiences of its speakers. This research is expected to contribute to the preservation of regional languages in Papua and enrich semantic studies in local linguistics.